Synaptonemal complex analysis of the Holstein-Friesian, Piemontese and Simmental breeds of Bos taurus taurus - Scavone, M. D.P. [UNESP]; Oliveira, C. [UNESP]; Trinca, L. A. [UNESP]; Foresti, F. [UNESP] (My University, 2001)
The synaptonemal complex (SC) of specimens of Bos taurus taurus from the Holstein-Friesian, Piemontese, and Simmental breeds, was analysed. The analysis included quantification of the frequency of various types of abnormalities in the SC, and the frequency of cells with SC abnormalities. All animals had 29 autosomal bivalents and one sexual bivalent and the most frequently recorded abnormality was pairing failure. The number of cells with abnormalities in the Holstein-Friesian breed was 29.41%, in the Piemontese breed was 30.00% and in the Simmental breed it was 29.54%. The subspecies Bos taurus taurus had 29.63% of cells showing abnormalities with 57.33% of these abnormalities occurring in zygotene and 42.67% occurring in pachytene. Statistical analyses showed that there were no significant differences in the number of cells with SC abnormalities among the breeds studied. The frequency of cells with abnormalities, and the efect on the fertility of the Holstein-Friesian, Piemontese and Simmental breeds are discussed.
Keywords: Bos taurus taurus; Cattle; Meiosis; Synaptonemal complex; Synaptonemal complex failure